Proximate composition of different portion of Hilsa, tenualosa ilisha from two regions of the Bay of Bengal in Bangladesh - Shamim, Md Ali Hossain; Ahmed, Md Kawser; Abdullah, Abu Tareq Mohammad (Dhaka University Journal of Biological Sciences, 2011)
Tenualosa ilisha from Chittagong and Khulna regions of the Bay of Bengal was analyzed which showed that proximate compositions varied among the different portions of fish body. The highest value of moisture found in dorsal portion of the fish (Khulna region) whereas the lowest value of moisture found in caudal portion of the fish (Chittagong region) were 56.59 and 54.69%, respectively. The protein content was estimated to be 20.56, 21.89, 20.29, 21.33, 20.87 and 20.50% in dorsal portion (Chittagong region), ventral portion (Chittagong region), caudal portion (Chittagong region), dorsal portion (Khulna region), ventral portion (Khulna region) and caudal portion (Khulna region), respectively. The fat content was recorded 18.66% in dorsal portion (Chittagong region), 20.28% in ventral portion (Chittagong region), 19.71% in caudal portion (Chittagong region), 18.65% in dorsal portion (Khulna region), 19.15% in ventral portion (Khulna region) and 19.00% in caudal portion (Khulna region). The percentage of ash content was highest in ventral portion of fish body from the Khulna region (1.55) and lowest in dorsal portion of fish body from the Khulna region (1.03). The highest carbohydrate content was found in caudal portion of fish from the Chittagong region (3.93%) and lowest in ventral portion of fish from the Chittagong region (1.60%). The present findings revealed that the highest protein content was recorded as in ventral portion of fish from the Chittagong region (21.89%) and the fat was highest in ventral portion of fish from the Chittagong region (20.28%). Key words: Proximate composition; Ecosystem; The Bay of Bengal DOI: http://dx.doi.org/10.3329/dujbs.v20i2.8970 DUJBS 2011; 20(2): 109-115